Assessment of the Admission and Follow-up Characteristics of Children Diagnosed with Secondary Osteoporosis - Emine Kübra Şen; Merih Berberoğlu; Gizem Şenyazar; Sirmen Kızılcan Çetin; Ayşegül Ceran; Seda Erişen Karaca; Elif Özsu; Zehra Aycan; Zeynep Şıklar (JCRPE)
INTRODUCTION: Secondary osteoporosis is a condition when the underlying disease or its treatment causes the bone mass to decrease and the bone structure to deteriorate, increasing the risk of fracture. The importance of diagnosis and treatment during childhood and adolescence is due to the long-term negative effects. In this study, our objectives were to determine the diagnostic findings, treatment efficacy, and follow-up characteristics of children with secondary osteoporosis. METHODS: Patients diagnosed with secondary osteoporosis between January 2000 and January 2021 were included. The research was a cross-sectional and descriptive study. Study participants had to be under 18 years of age when the primary underlying disease was diagnosed and had received treatment for secondary osteoporosis. Patient data were collected from patient files. Statistical analysis was performed using Statistical Package for the Social Sciences, version 20.0 (IBM Corp, Armonk, NY, USA). RESULTS: Sixty-one patients (28 female; 45.9%) were evaluated. The most common underlying primary diseases were inflammatory diseases (57.7%), neuromuscular diseases (26.2%), immunodeficiency (13.1%), acute lymphoblastic leukemia (8.2%), metabolic diseases (8.2%), solid organ transplantation (8.2%), bone marrow transplantation (6.6%) and epilepsy (6.6%). The mean±standard deviation chronological age when secondary osteoporosis was diagnosed was 11.89±4.88 years. Patients were evaluated for osteoporosis at a mean of 6.39±5.13 years after the onset of the underlying primary chronic diseases. Most (78.7%) had a history of one or more chronic drug use, including systemic steroids (59%), chemotherapeutics (23%), immunomodulatory drugs (19.7%), antiepileptic drugs (8.2%), inhaled steroids (4.9%), intravenous immunoglobulin (1.6%), and antituberculosis drugs 1.6%.Bone pain was detected in 49.2%. All patients had vertebral fractures before treatment. Bisphosphonate treatment was given to 45 (73.8%). There was a significant increase in mean bone mineral density (BMD) and bone mineral content six months after treatment (both p<0.001). There was a significant increase in BMD Z-score values for chronological and height age (both p<0.001). Overall mean BMD values increased by 31.15% with treatment. Following bisphosphonate treatment, there was a significant reduction in both fracture number and bone pain (p<0.01). Similar benefits from bisphosphonate treatment were evident in those who did or did not receive steroid treatment. DISCUSSION AND CONCLUSION: Secondary osteoporosis is a condition that is influenced by many factors, such as the primary disease causing osteoporosis and chronic medication use, especially steroids. If left untreated, osteoporosis may lead to clinically important morbidity (bone pain, fractures, immobilization) and reduced linear growth of bone. When used to treat childhood secondary osteoporosis, bisphosphonates significantly improve BMD and reduced fracture risk.